Long-Term and Multipoint Observations of Atmospheric Heavy Metal (Cu and Cd) Deposition and Accumulation in Soil–Crop System and Human Health Risk Evaluation Around a Large Smelter - Zhou, Jun; Cui, Hongbiao; Zhu, Zhengqiu; Liu, Mengli; Xia, Ruizhi; Liu, Xiaoli; Ding, Chengcheng; Zhou, Jing (Exposure and health, 2024)
The atmospheric deposition of copper (Cu) and cadmium (Cd) was monitored over 79 months to investigate the fluxes and influencing factors and to partition the possible health risk between new deposition and legacy heavy metals in ten locations surrounding a Cu smelter. The results showed annual Cu and Cd deposition fluxes ranged from 7.6- to 81-folds (113–1309 mg m –2 ) and from 2.7- to 12-folds (2.8–9.5 mg m –2 ) higher than those in the background site, respectively. The direct exposure to heavy metals via inhalation of the atmospheric deposition was negligible, but the indirect exposure from new deposition and then accumulation in crops via dietary crop intake was the primary pathway. Principal component analysis (PCA) and redundancy analysis showed the rate of wind frequency and distance to the point source were critical driving factors affecting the spatial flux distribution. High atmospheric deposition and legacy soil contamination resulted in rice Cd concentrations higher than the national thresholds and rice ingestion was the primary exposure pathway. Multiple pathways provided potential non-carcinogenic risk posed by Cu and Cd, especially for Cd. Current atmospheric deposition via indirect exposure contributed to about 40% of the non-carcinogenic risk, although it only accounted for 0.22–0.88% and 0.96–2.5% of Cu and Cd pools in the soil plow layer (0–20 cm). Legacy soil Cu and Cd contributed 60% of the non-carcinogenic risk. These findings implicate that reduction of anthropogenic emission and atmospheric deposition should be considered as effective environmental management to reduce the human heavy metal exposure in typical areas influenced by substantial deposition loads.